Komunikasi Kesehatan Antara Apoteker Dan Pasien Terhadap Diberhentikannya Obat Sirup Paracetamol Anak Di Apotek K24 Vienna Gading Serpong Tangerang - Subekti, Jesiana Dwi; Wati, Lina; Mirza, Mochammad (Peneliti.net, 2024)
This research is entitled Health Communication Between Pharmacists and Patients Against Discontinuation of Children's Paracetamol Syrup at K24 Pharmacy Vienna Gading Serpong Tangerang. Health communication is a process of delivering health information to encourage changes in individual and group behavior in order to improve health status. Health communication is used as a prevention effort and a solution in dealing with cases of kidney failure that occur in children due to consumption of children's paracetamol syrup which contains dangerous ingredients which are carried out at the K24 Vienna Pharmacy Gading Serpong Tangerang. This study aims to determine the role of health communication between pharmacists and patients in drug purchasing services at pharmacies in the discontinuation of children's hennaetamol syrup. The type of research used is a qualitative research method and the type of research used is descriptive. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, data triangulation and conclusions. The results of the study show that the health communication used by pharmacists to patients is good and in accordance with the rules that have been set according to prevention, finding solutions and avoiding additional cases of kidney failure in children. Health communication has been proven to bring changes to the knowledge, attitude and behavior of patients and the community in responding to cases of paracetamol syrup for children which causes kidney failure.